Correction: A multi-component reaction for the synthesis of pyrido [1, 2-b] isoquinoline derivatives via the [3 + 2] cycloaddition reaction between alkynes and in situ generated isoquinolinium ylides. Issue 42 (21st October 2020) - Shinde, Sundar S.; Laha, Soumi; Tiwari, Dharmendra K.; Sridhar, B.; Likhar, Pravin R.
Abstract : Correction for 'A multi-component reaction for the synthesis of pyrido [1, 2- b ] isoquinoline derivatives via the [3 + 2] cycloaddition reaction between alkynes and in situ generated isoquinolinium ylides' by Sundar S. Shinde et al., Org. Biomol. Chem., 2019, 17, 4121–4128, DOI: ; 10.1039/C9OB00560A .